IMPLEMENTATION OF NEWMAN METHOD FOR ANALYZING STUDENT ERRORS IN SOLVING HOTS TYPE MATH PROBLEMS - Mawaddah Mawaddah; Abdillah Abdillah; Sirajuddin Sirajuddin; Mahsup Mahsup (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Critical thinking ability is one of the skills required for study, but in reality, the thinking ability of Indonesian students is still very low. Students' problem-solving skills in math classes, especially HOTS problems, have weaker developmental abilities, leading to difficulties and mistakes in solving problems in the form of stories.The purpose of the study was to describe the mistakes students make when using the Newman method to solve HOTS-type math problems. This study used qualitative and descriptive methods. The subjects of this study were 13 students in twelve classes of senior high school. Data collection techniques in the form of tests, interviews, and documents. Data validity using triangulation methods using interviews, observations, and survey methods.The results showed working on the problem of three-dimensional material stories, and statistical percentage of errors was mostly done at the writing stage of the final answer with a percentage of 90.38. followed by misrepresenting with a percentage of 61.53%, then transformation errors and process errors with a percentage of 23.07%, and error reading problems as much as 1.85%.